A Grounded Theory of Text Revision Processes Used by Young Adolescents Who Are Deaf. (April 2014) - Yuknis, Christina
This study examined the revising processes used by 8 middle school students who are deaf or hard-of-hearing as they composed essays for their English classes. Using grounded theory, interviews with students and teachers in one middle school, observations of the students engaging in essay creation, and writing samples were collected for analysis. Constant comparison was used during open, axial, and selective coding to develop the grounded theory. Two major themes emerged as central concepts to the students' revision processes: Interacting with Language and Interacting with Instruction. Findings indicate that students did not participate much in revising their texts and teachers assumed most of the cognitive burden of writing. These findings are reported along with implications for practice and research.